2021
DOI: 10.3389/fphar.2021.747991
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine A Induces Cardiac Developmental Toxicity in Zebrafish by Up-Regulation of Wnt Signaling and Oxidative Stress

Abstract: Due to the widely application of Cyclosporine A (CsA) as an immunosuppressant in clinic, it is necessary to study its potential toxicity. Therefore, we used zebrafish as a model animal to evaluate the toxicity of CsA on embryonic development. Exposure of zebrafish embryos to CsA at concentrations of 5 mg/L, 10 mg/L, and 15 mg/L from 12 hpf to 72 hpf resulted in abnormal embryonic development, including cardiac malformation, pericardial edema, decreased heart rate, decreased blood flow velocity, deposition at y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…This finding was consistent with the previous reports that the reduced levels of the tbx2b gene inhibited cardiac proliferation [22]. We also performed H&E staining of the paraffin sections of the heart and found that the heart was significantly linearized, whereas the number of cardiomyocytes was significantly reduced [19]. This observation suggested that the abnormal zebrafish heart development caused by PCNB might be due to the decreased proliferation of heart cells and substantial reduction in the ability of the heart to loop.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding was consistent with the previous reports that the reduced levels of the tbx2b gene inhibited cardiac proliferation [22]. We also performed H&E staining of the paraffin sections of the heart and found that the heart was significantly linearized, whereas the number of cardiomyocytes was significantly reduced [19]. This observation suggested that the abnormal zebrafish heart development caused by PCNB might be due to the decreased proliferation of heart cells and substantial reduction in the ability of the heart to loop.…”
Section: Discussionsupporting
confidence: 92%
“…All zebrafish breeds were obtained from the National Zebrafish Resource Center and were raised under standard temperature (28 ± 1 • C) and 14 h light:10 h dark photoperiod conditions according to the Institutional Animal Care and Use Committee. Breeding zebrafish requires water with a pH of 7 and a conductivity of 500 µS/cm, feeding at 9:00 a.m. and 2:00 p.m. every day with brine shrimp larvae [19]. All zebrafish embryos were euthanized by ice bath after experimentation.…”
Section: Zebrafish Strains and Rearingmentioning
confidence: 99%
See 1 more Smart Citation
“…The downregulation of cell cycle key genes ccne1, cdk2, cdk6, and the upregulation of ccnd1 suggested that cell proliferation was also seriously affected by the disordered expression of these genes. According to previous publications, excessive accumulation of ROS leads to oxidative stress, affects mitochondrial function, hinders cell proliferation, and further promotes cell apoptosis (Bai et al, 2021;Wan et al, 2021). Therefore, the apoptosis of zebrafish skeletal cells exposed to cysteamine was probably mediated by oxidative stress.…”
Section: Discussionmentioning
confidence: 92%
“…The heart of zebrafish larvae was then imaged with inverted microscopy (Olympus IX83, Japan) (Supplementary Figure S1). The pericardial area, the venous congestion area (Lu et al, 2020), and the distance between the sinus venosus and bulbus arteriosus (SV-BA) of the heart (Wan et al, 2021) were counted by Image Pro Plus5.1 software. The data were analyzed by one-way analysis of variance (ANOVA) using GraphPad Prism 6.01 software and expressed as the mean ± standard error (SE).…”
Section: Biological Activities Of the American Ginseng Samples On The...mentioning
confidence: 99%